ANALISIS PENGARUH KESELAMATAN DAN KESEHATAN KERJA (K3) TERHADAP KINERJA PEKERJA PADA PROYEK PEMBANGUNAN RUMAH SAKIT PRATAMA DESA HITU KABUPATEN MALTENG - Ramona Fitra Sari Lating; Rudi Serang; Wellem Gaspersz; Delvia Rimesye Apalem; Abraham Tuanakotta (Journal Agregate, 2023)
Occupational Safety and Health (K3) is a science for anticipating, recognizing, evaluating and controlling hazards that arise in the workplace that can impact the health and welfare of workers. The risk of falling is the highest cause of accidents. The use of adequate safety equipment such as guardrails and helmets, as well as the implementation of security procedures such as inspection of non-permanent stairs and scaffolding can reduce the risk of accidents. occupational health on work performance (K3) in the Hitu Village Primary Hospital Development project. Analysis of the data used to calculate the analysis of the application of health and work to the project "Construction of the Hitu Village Pratama Hospital". f test. Based on the results of the analysis it was found that safety (X1) and health (X2) had a positive effect on work performance from the results of testing multiple linear regression analysis from the correlation table or partial correlation, where safety (X1) obtained a value of r = 0.766 with a significance of 0.000 < 0.05 Health (X2) obtained a value of r = 0.592 with a significance of 0.000 <0.05 For the Summary Regression Correlation Model (R) which simultaneously (together) between the variables Health (X1) and Safety (X2) , on Work Performance (Y) a value of r = 0.767 is obtained. Between the two aspects of safety and health on the work performance of the Hospital Development project Hitu Village Primary kit, the most dominant influence from the results of the partial test is the work safety aspect of 0.722 or 72.2%.